Evaluation of Drug Management of Pharmacy Installation at Universitas Sumatera Utara Hospital (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
Evaluation of Drug Management of Pharmacy Installation at Universitas Sumatera Utara Hospital